A Green Economy Approach to Solid Waste Management in Minna, Nigeria - Yekeen Adeeyo Sanusi; Sundat Gideon Owoyele; Samuel Medayese; Ndana Tanko Mohammed (Forum Geografi, 2022)
This study is based on solid waste recycling activities in Minna, Nigeria. This study examines the potential for waste recycling to provide livelihood opportunities in Nigeria. The study identified two recycling centres in Minna and collected data through direct observation, measurements, questionnaire administration, and interviews. The collected data was analyzed using statistical packages for social sciences and livelihood approach to demonstrate the green value of recycling, identify impediments to green growth, and map the recycling cluster. The result shows that the recycling cluster occupies an area of 0.64 hectares that accommodates 141 recycling outlets, with about 40% of the outlets occupying below the standard shop size of 7.2m2. The recycling outlets use 18 types of recovered materials to reproduce 27 varieties of products. Each recycling outlet engages about 3.4 persons and offers training to an average of 6 persons each. The study highlights the importance and potential of informal solid waste recycling as a sub-sector that fulfils social, economic, and environmental benefits associated with sustainable development. However, the lack of commitment by governments to waste recycling undermines the contribution of the recycling business. Moving towards the zero-waste policy can save public funds that can be invested in the waste disposal and reduce the threat to public health from solid waste. Furthermore, safety measures should be ensured among the scavengers and the recyclers, and the physical environment of the recycling cluster should be upgraded to take care of poor accessibility and the use of makeshift structures by most of the recycling units. Governments should focus on policies that encourage waste sorting, collection, sales, and solid waste processing at all scales. We underscore the need for creative and reliable government support to achieve green growth and development in the solid waste recycling sector.